Relationship between backpack weight and incidence of low back pain in senior high students - Djajasasmita, Daswara; Jacob Manoe, Zacarja; Wulandari, Feby (ACTA Medical Health Sciences, 2023)
Low back pain (LBP) is one of the most common musculoskeletal disorders that can impair daily activities. The causes of LBP are mostly non-specific, including the abnormalities in the soft tissues or form of muscles, ligament injuries, and muscle spasms or fat igue. One of the causes of LBP is carrying excess weight. If the load carried exceeds 15% of body weight, the person who carried the weight will experience musculoskeletal disorders. Students may carry a backpack with a weight that exceeds the recommended weight and this weight will put pressures on the muscles, ligaments, and tendons, causing tension and acute neck pain. These students then will have a higher risk of suffering LBP. The aimed of this study was to identify the relationship between the backpack load and the incidence of low back pain in students. Using the cross-sectional analytical method, this study was performed on a total of 63 students from a senior high school in Cimahi, Indonesia. Subjects were selected using the multistage random sampling and data on the sociodemographic, backpack load, and low back pain were collected and analyzed using the chi-square test. Results showed that 45 students (71.4%) experienced LBP, while the average weight of the backpack carried by these students 6.59 kg (p <0.001). Thus, there is a significant relationship between the excessive backpack weight and the incidence of LBP among students. DOI : 10.35990/amhs.v1n3.p105-111 REFERENCES Amyra Natasha A, Ahmad Syukri A, Siti Nor Diana MK, Ima-Nirwana S, Chin KY. The association between backpack use and low back pain among pre-university students: A pilot study. J Taibah Univ Med Sci. 2017;13(2):205-9. Walsh E. Finite Element Analysis. Section I, Chapter 11. Elsevier; 2017. p. 168. Barkhordari A, Ehrampoush MH, Barkhor M. Assessment of school backpack weight and other characteristics in elementary schools, Yazd, Iran. J Community Health Res. 2013;2(1):2-7. Epidemiologic features of chronic low-back pain. The National Musculoskeletal Medicine Initiative; 2000. p. 585. Cooper P. Low Back Pain. Clinical Reference System. McKesson Health Solution LLC; 2003. p. 16. Bener A, Alwash R, Gaber T, Lovasz G. Obesity and low back pain. Coll Antropol. 2003;27(1):95-104. Kędra A, Czaprowski D. Epidemiology of back pain in children and youth aged 10–19 from southeast Poland. Biomed Res Int. 2013;2013:506823. Rahmi SA. Analisis faktor sedentary lifestyle dan konsumsi jajanan terhadap kejadian stunted obesity pada anak sekolah dasar di Kabupaten Magelang [dissertation]. Universitas Negeri Semarang; 2020. Wheeler A. Low back pain and sciatica. 2013. Available from: https://www.researchgate.net/publication/300909291_Low_Back_Pain_and_Sciatica Fathoni H, Handoyo, Swasti KG. Hubungan sikap dan posisi kerja dengan low back pain pada perawat di RSUD Purbalingga. Jurnal Keperawatan Soedirman. 2012;7(2). Lailani TM, Dewi DRL, Handoko W. Hubungan antara peningkatan indeks massa tubuh dengan kejadian nyeri punggung bawah pada pasien rawat jalan di poliklinik saraf RSUD Soedarso Pontianak. Dokter. 2013;3(1). Moore KL, Dalley AF. Anatomi berorientasi klinis. 5th ed. Vol. 2. 2013. Tortora GJ, Derrickson BH. Principles of anatomy and physiology. 12th ed. Danvers: John Wiley & Sons; 2009. Guyton AC, Hall JE. Buku ajar fisiologi kedokteran. 11th ed. Rachman RY, Hartanto H, Novrianti A, Wulandari N, editors. Jakarta: EGC; 2007. Battié MC, Videman T, Levalahti E, Gill K, Kaprio J. Heritability of low back pain and the role of disc degeneration. Pain. 2007;131(3):272-80. Siivola SM, Levoska S, Latvala K, Hoskio E, Vanharanta H, Keinänen-Kiukaanniemi S. Predictive factors for neck and shoulder pain: A longitudinal study in young adults. Spine (Phila Pa 1976). 2004;29(15):1662-9. Alghamdi RS, Nafee H, El-Sayed A, Alsaadi SM. A study of school bag weight and back pain among intermediate female students in Dammam City, Kingdom of Saudi Arabia. J Nurs Educ Pract. 2018;8(12):105. Ernawati TS, Andriani R, Yanti SN. Hubungan penggunaan tas ransel terhadap kejadian nyeri punggung bawah pada siswa kelas IX Madrasah Tsanawiyah Negeri 2 Pontianak. Jurnal Cerebellum. 2016;2(2):468-78. Dumondor SV, Angliadi E, Sengkey L. Hubungan penggunaan ransel dengan nyeri punggung dan kelainan bentuk tulang belakang pada siswa di SMP Negeri 2 Tombatu. E-CliniC. 2015;3(1). Al Fageeh A. The effect of school bag weight on pain, posture, and vital capacity of lung of elementary school students in Bethlehem District, Palestine. Middle East J Family Med. 2009;7(7):7-14. Keselamatan dan kesehatan kerja: Manajemen dan implementasi K3 di tempat kerja. Surakarta: Harapan Press; 2008.